2023
DOI: 10.3390/nu15051274
|View full text |Cite
|
Sign up to set email alerts
|

Association between Intra- and Extra-Cellular Water Ratio Imbalance and Natriuretic Peptides in Patients Undergoing Hemodialysis

Abstract: Natriuretic peptides are associated with malnutrition and volume overload. Over-hydration cannot simply be explained by excess extracellular water in patients undergoing hemodialysis. We assessed the relationship between the extracellular and intracellular water (ECW/ICW) ratio, N-terminal pro-B-type natriuretic peptide (NT-proBNP), human atrial natriuretic peptide (hANP), and echocardiographic findings. Body composition was examined by segmental multi-frequency bioelectrical impedance analysis in 368 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…25 Regarding the role of natriuretic peptides, previous studies have identified a potential association between these markers and malnutrition. [26][27][28][29] The association between high concentrations of natriuretic peptides and malnutrition is likely explained by their role as markers of congestion and hence gut oedema, malabsorption, and inflammatory activation. In the context of advanced HF, very-high levels of natriuretic peptides (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Regarding the role of natriuretic peptides, previous studies have identified a potential association between these markers and malnutrition. [26][27][28][29] The association between high concentrations of natriuretic peptides and malnutrition is likely explained by their role as markers of congestion and hence gut oedema, malabsorption, and inflammatory activation. In the context of advanced HF, very-high levels of natriuretic peptides (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, bioelectrical impedance analysis is useful to assess body composition, identify malnutrition and perform close and targeted patient monitoring 25 . Regarding the role of natriuretic peptides, previous studies have identified a potential association between these markers and malnutrition 26–29 . The association between high concentrations of natriuretic peptides and malnutrition is likely explained by their role as markers of congestion and hence gut oedema, malabsorption, and inflammatory activation.…”
Section: Discussionmentioning
confidence: 99%
“…This is a sub-analysis study of patients who consented to a QOL questionnaire in our previous cross-sectional study. The detailed study design has been published elsewhere [18]. Participants were recruited from four maintenance hemodialysis clinics (Seijinkai Mihama Hospital, Seijinkai Mihama Sakura Clinic, Seijinkai Narita Clinic, and Seijinkai Katori Clinic) between 2019 and 2022.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…During the use of a permanent catheter for dialysis initiation and maintenance, patients often experience malfunction and infection of the catheter [7,8]. Several previous studies examined the extracellular-to-total body water (ECW/TBW) and extracellular-to-intracellular water (ECW/ICW) ratios in patients receiving maintenance HD [9][10][11][12][13][14]. However, fewer studies have investigated the association of permanent catheter patency survival with those parameters.…”
Section: Introductionmentioning
confidence: 99%